Managerial accounting - Heitger, Lester E.; Matulich, Serge (New York : McGraw-Hill, 1980)
This book is the managerial accounting volume of a coordinated two-volume financial/managerial set designed for introductory accounting courses. the book is suitable for schools that cover undergraduate or graduate managerial accounting either as a semester or quarter, or in combination with financial accounting over the academic year.
Includes bibliographical references and index.
hza 23/08/2018
Loans
Keywords: Managerial accounting; Financial Accounting